Моделювання випромінювання черенкова в пакеті МЕЕР - Нєвров, В. Ю. (ХНУРЕ, 2019)
Model of the Cherenkov radiation is considered in this work. Package MEEP is used for numerical calculations of the radiation field spatial distribution. Twodimensional model is used for modeling of Cherenkov radiation. Different values of the charged particle velocity are considered for visualization of the radiation fields